The Description of Prolanis Patient Satisfaction Towards Prolanis Management - Dimas Caesar Kurniawan (Jurnal Admmirasi, 2021)
Primary healthcare should have standard to maintenance and increase the service quality in order to manage patients with chronic disease, especially for patients with chronic disease that been carried out by BPJS called as Prolanis. This study aims to know is service quality affect to the successful of Prolanis therapy management in Bantul. This research used a descriptive analytic. The study sample was all patients who join Prolanis Club in Klinik Pratama IDI Bantul. The sample was 50 people. This study showed prolanis patient satisfaction in both criteria success and unsuccess are satisfied in each dimension (Tangible, Responsiveness, Reliability, Empathy and Assurance). The result of this study showed that the description of prolanis patients’ satisfaction towards prolanis management is good.